THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON THE COMPANY’S FINANCIAL PERFORMANCE (An Empirical Study on Mining Companies enlisted in ISE during 2014) - Eskasari Putri; Arief Budhi Dharma; Rina Trisnawati (Equilibrium : Jurnal Ilmiah Ekonomi, Manajemen dan Akuntansi, 2020)
AbstractThis research aimed to provide empirical evidence that the disclosure of Corporate Social Responsibility affected significantly the Return On Asset (ROA), Return On Equity (ROE), and Return On Sales (ROS) in mining companies enlisted in ISE during 2014. The sample of research was taken using purposive sampling method; the data was obtained from www.idx.com. The sample of research consisted of companies in mining sector during 2014. There were 33 companies fulfilling the criteria of sample. The method of analyzing data used in this research was a simple regression analysis. Considering the result of research using t-test, it could be found that the disclosure of Corporate Social Responsibility affected ROA and ROE positively and insignificantly, while it affected ROS positively and significantly. The recommendations given to the company were that the company should disclose the activities related to its Corporate Social Responsibility more transparently in its annual report, Corporate Social Responsibility indeed needed large cost, but it could benefit the company as well by improving the company’s image and legitimacy, so that the company could make it the corporate strategy.Keywords: CSR, ROA, ROE, ROS